Erika (Local Wisdom E-module) Dhadak Merak Dance on Newton’s Material - Choirunnisa', Adinda; Kholiq, Abd (Jurnal Pembelajaran Fisika, 2023)
The research carried out is development research which aims to produce e-modules based on local wisdom that are declared feasible. Feasibility is reviewed based on validity, practicality and effectiveness. This development research uses the Hannnafin & Peck model by going through three stages, namely needs assessment, design and development as well as implementation. In terms of validity, an average percentage of 93.45% is obtained with a very valid category. Practical results were obtained from the implementation and learning constraints by using Erika (local wisdom e-module) Dhadak Merak Reog Ponorogo dance which was stated to be practical. The implementation of learning using Erika gets 91.67% results in a very good category. The results of process-based activities using e-modules in learning obtained an average percentage of 75.71 in the good category. The effectiveness of student learning outcomes has increased with an average n-gain score of 0.3 in the moderate category. The results of student responses to learning using Erika (local e-module) Dhadak Merak Reog Ponorogo Dance obtained an average percentage of 87.59% in the very good category. Thus Erika (local wisdom e-module) Dhadak Merak Reog Ponorogo Dance on Newton's Law material is declared suitable for use in terms of validity, practicality, and effectiveness to be applied in learning.